We need to talk—how muscle stem cells communicate - Majchrzak, Karolina; Hentschel, Erik; Hönzke, Katja; Geithe, Christiane; von Maltzahn, Julia (Frontiers in Cell and Developmental Biology, 2024)
Skeletal muscle is one of the tissues with the highest ability to regenerate, a finely controlled process which is critically depending on muscle stem cells. Muscle stem cell functionality depends on intrinsic signaling pathways and interaction with their immediate niche. Upon injury quiescent muscle stem cells get activated, proliferate and fuse to form new myofibers, a process involving the interaction of multiple cell types in regenerating skeletal muscle.Receptors in muscle stem cells receive the respective signals through direct cell-cell interaction, signaling via secreted factors or cell-matrix interactions thereby regulating responses of muscle stem cells to external stimuli. Here, we discuss how muscle stem cells interact with their immediate niche focusing on how this controls their quiescence, activation and self-renewal and how these processes are altered in age and disease.